Neural Correlates of Social Perception Deficit in Schizophrenia: An Event-related Potential Study - Jiang-juan Li; Xin-ping Li; Jia-min Han; Yi-fan Sun; Xiao-hong Liu; Xue-zheng Gao; Li-min Chen; Zhen-he Zhou; Hong-liang Zhou (Journal of Integrative Neuroscience)
Background: Deficits in emotion recognition have been shown to be closely related to social-cognitive functioning in schizophrenic. This study aimed to investigate the event-related potential (ERP) characteristics of social perception in schizophrenia patients and to explore the neural mechanisms underlying these abnormal cognitive processes related to social perception. Methods: Participants included 33 schizophrenia patients and 35 healthy controls (HCs). All participants underwent electroencephalogram recording while completing the Emotion Intensity Recognition Task (EIRT). Behavioral data and ERP components were analyzed using repeated measures analysis of variance. Results: Schizophrenia patients had longer reaction times (RTs) to sad faces compared with disgusted faces, and had lower accuracy than the HCs. Additionally, schizophrenia patients had lower accuracy than the HCs for disgusted faces, surprised faces, angry faces, and fearful faces. Late Positive Potential (LPP) mean amplitudes of the HCs were larger than the schizophrenia patients for sad faces in the frontal lobe and central lobe. For happy faces, the HCs elicited larger LPP mean amplitudes than schizophrenia patients in the frontal lobe and central lobe. For surprised faces, the LPP mean amplitudes were higher in the HCs in the central lobe and parietal lobe than in schizophrenia patients. The HCs exhibited larger LPP mean amplitudes for angry faces in the frontal lobe, central lobe, and parietal lobe than in schizophrenia patients. For fearful faces, the HCs elicited a larger LPP mean amplitude than schizophrenia patients in the frontal lobe, central lobe, and parietal lobe. Conclusions: Schizophrenia patients present impaired social perception, and the observed ERP patterns provide valuable insights into the neural mechanisms underlying the EIRT results, highlighting the differences between HCs and schizophrenia patients. These findings underscore the potential of the EIRT as a biomarker for cognitive and emotional dysregulation in schizophrenia. Clinical Trial Registration: No: ChiCTR2300078149. Registered 29 November, 2023; https://www.chictr.org.cn/showproj.html?proj=211510.